Unsur-Unsur Intrinsik Pendidikan Tauhid Dalam Cerpen Robohnya Surau Kami Karya A . A Navis - Sulung Aji Pangestu, Sulung Aji Pangestu (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2022)
Abstract The short story The Collapse of Surau Kami by A. A Navis is a short story which contains elements of monotheism education. A. A Navis is a writer from West Sumatra who is known as an outspoken figure, A.A. Navis in writing is focused on human and human problems such as suffering, bitterness, happiness and hope. This is done on the basis of intellectual awareness and not on the basis of any particular interest. The presence of A. A Navis in the world of Indonesian literature is considered not only as a great author, but also an author who voices the voice of Sumatra. This research is focused on the element of monotheism education in the short story "Robohnya Surau Kami". The type of research used is library research (Library Research). The approach used is the same as the qualitative research method, namely the research method carried out in an effort to present the social world and its perspective in terms of concepts, behavior, and human problems being studied. Furthermore, the data were analyzed using content analysis. The results of this study indicate that the intrinsic elements of Tawhid education such as: theme, plot, characters or characterizations, background or setting in the short story The Collapse of Surau Kami can be reflected in it. Through the short story The Collapse of Surau Kami, readers will be moved and get a lot of learning from the characters. Thus, the short story The Collapse of Surau Kami is a short story worthy of being used as a medium for studying monotheism education. Keywords: Unsur-Unsur Intrinsik, Pendidikan Tauhid, Cerpen Robohnya Surau Kami. Abstrak Cerpen Robohnya Surau Kami karya A. A Navis ini merupakan sebuah cerpen yang didalamnya mengandung unsur pendidikan tauhid. A. A Navis adalah seorang sastrawan yang berasal dari Sumatera Barat yang dikenal sebagai sosok yang ceplas-ceplos, A.A. Navis dalam menulis tertuju pada persolan manusia dan kemanusiaan seperti, penderitaan, kegetiran, kebahagiaan dan harapan. Hal demikian dilakukan atas dasar kesadaran intelektual dan bukan atas dasar kepentingan tertentu. Kehadiran seorang A. A Navis di dunia sastra Indonesia dianggap bukan hanya sebagai pengarang besar, tetapi juga seorang pengarang yang menyuarakan suara Sumatera. Penelitian ini difokuskan pada unsur pendidikan tauhid pada cerpen Robohnya Surau Kami. Jenis penelitian yang digunakan adalah penelitian pustaka (Library Researh). Pendekatan yang digunakan sama dengan metode penelitian kualitatif yaitu metode penelitian yang dilakukan dalam upaya untuk menyajikan dunia sosial maupun prespektifnya dari segi konsep, perilaku, serta persoalan manusia yangg diteliti. Selanjutnya data di analisis dengan menggunakan countent analysis. Hasil penelitian ini menunjukan bahwa unsur-unsur intrinsik pendidikan Tauhid seperti : tema, alur, tokoh atau penokohan, latar atau setting dalam cerpen Robohnya Surau Kami dapat terceminkan didalamnya. Melalui cerpen Robohnya Surau Kami pembaca akan tergugah dan mendapatkan banyak pembelajaran dari tokoh-tokohnya. Dengan demikian, cerpen Robohnya Surau Kami merupakan cerpen yang layak dijadikan media untuk mempelajari pendidikan tauhid. Kata Kunci : Unsur-Unsur Intrinsik, Pendidikan Tauhid, Cerpen Robohnya Surau Kami.